Illegal Dumping as an Indicator for Community Social Disorganization and Crime - Brandt, Amory Anne (2017)
Illegal dumping of household waste in and around city streets results in many negative health, economic, and environmental effects. This goal of this study was to understand the systemic causes of illegal dumping within San José, California. Illegal dump sites were identified, quantified, characterized, and mapped within urban census block groups at a range of median family income levels. Results showed that commonly dumped debris types were furniture, and garbage. The most illegal dumping occurred within census block groups with low median family incomes, high percentages of non-English speaking individuals, and high percentages of renters. Factors such as social disorganization, inequitable levels of garbage service, and lack of awareness of free city programs could be causing illegal dumping within San José. Illegal dumping was also more prevalent in areas with occurrences of petty crime. This study concluded that illegal dumping has the potential to serve as a visual representation of social disorganization and crime within communities